Effects of Statistical and Narrative Health Claims on Consumer Food Product Evaluation - Hung-Chou Lin; Sheng-Hsien Lee (Frontiers in Psychology, 2021)
This research aims at exploring the underlying mechanisms how consumers respond to statistical and narrative health claims when they evaluate food products. Moreover, personality traits and product-related information are also incorporated to discuss their effects on the relationship between message types and consumers’ food product evaluation. The results indicate that statistical health claims are more persuasive than narrative health claims. In addition, the results show that individuals’ health knowledge, NFC moderate the relationship between message types and product evaluation. It argues that individuals with limited health knowledge evaluate food product more favorably when statistical health claims are used, while individuals with more health knowledge evaluate food product more favorably when narrative health claims are used. Moreover, it reveals that individuals with high NFC evaluate food product more favorably when statistical health claims are used, while individuals with low NFC evaluate food product more favorably when narrative health claims are used.